Expression of Sarcoptes scabiei Exon 5 Tropomyosin Gene as an Attempt to Develop Recombinant Antigen for Scabies Diagnosis - Alfin Harjuno Dwiputro; Taufik Mulya Perdana; Tri Baskoro Tunggul Satoto; Wayan Tunas Artama (Jurnal Kedokteran Diponegoro)
Background: Scabies diagnosis is greatly influenced by the experience of the examiner, since the diagnosis is rely on a complex diagnostic criteria. Antigen detection test is an alternative technique for diagnosing scabies in the future. Tropomyosin is a highly conserved protein which expressed by Sarcoptes scabiei mites.